Determinant Analysis of Hand Hygiene Compliance and Its Relation to HAIs in Hospitals: Systematic Literature Review - Fitriani, Fitriani; Rondhianto, Rondhianto; Ismara, Ketut Ima (Poltekkes Kemenkes Palu, 2024)
Hand hygiene is one of the practical steps that healthcare providers can take to reduce the incidence of HAIs or nosocomial infections. The percentage of hand hygiene compliance is still low, between 35-55.3%. Several previous studies showed that many factors cause hand hygiene adherence. However, the results are still varied, so this study aimed to determine the factors of hand hygiene, determine the factors that most influence hand hygiene adherence, and the link between hand hygiene and the incidence of HAIs in hospitals. This systematic literature review follows the PRISMA protocol guidelines in three electronic databases (PubMed, Science Direct, and Google Scholar). Article quality was assessed using the JBI assessment tool and analyzed using meta-synthesis. The inclusion criteria are articles discussing hand hygiene compliance among hospital nurses and articles published in 2021-2023, so 15 selected papers. The determinants of hand hygiene compliance include knowledge, attitude, motivation, supervision from superiors or related parties, facilities, age, gender, years of service, and feedback. An electronic monitoring system also has significantly affected hand hygiene compliance. Several articles stated that the multimodal approach initiated by WHO positively impacted hand hygiene compliance. The most dominant factor is the knowledge variable. Hand hygiene compliance is closely related to the incidence of HAIs, when hand hygiene compliance is high, it can reduce the incidence of HAIs in health services.